Evaluation of chemical and physical characteristics and functional silage corn (Zea Mays) and silage sorghum (Sorghum vulgare). Urdaneta Municipality Lara State (Agroindustria, Sociedad y Ambiente, 2013)
Silage is a benefit in livestock production, supplies the nutritional requirements of a commercial supplement natural food derived from vegetable crops. The purpose of this research was to evaluate the physicochemical and functional characteristics of corn silage and sorghum silage samples of silage sorghum ( A) and maize (B ) were taken were obtained from the production unit Finca Santa Paula Municipal Urdaneta Lara State. Each physicochemical and functional analyzes were performed in triplicate . T test " studentd " ( P
Keywords: fermented food; Vegetable crops; silage